Multistakeholder learning alliances for “collaborative entrepreneurship” strategy - Gonsalves, Julian Francis (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
Strategy to improve the uptake of postharvest technologies through alliances that examine a range of technical, end-user learning, and market support needs in postharvest systems. Characterized by participatory 'learning-by-doing' approach that allows all stakeholders to identify particular sources of postharvest losses and a range of mitigating technology options for piloting and verification; as well as allow the realization of working together to support the adoption of new technologies. IRRI has established national learning alliances in Cambodia, Vietnam, and the Philippines.